Estratégias comunicacionais para a mobilização da responsabilidade social empresarial: a atuação do Instituto Ethos no pacto empresarial pela integridade e contra a corrupção - Martins, Amanda Frick (2017)
The present research aims to analyze the communication strategies of the ETHOS Institute for the mobilization of corporate social responsibility. For this, we investigated the initiative titled Corporate Pact for Integrity and Against Corruption, promoted by the Institute. In addition, we have opted to analyze three companies that are signatories of the Pact that have their offices in the state of Rio Grande do Sul. We enclose, as specific objectives, to understand the initiative of the Business Pact for Integrity and Against Corruption; to recognize the communication strategies promoted by the ETHOS Institute in the Pact against Corruption and to measure the strategies adopted by the signatory companies for the implementation and maintenance of the corporate social responsibility actions proposed by the Pact. The methodology applied in the research was qualitative, descriptive, interpretative and of a cyclical nature. The methodological proposal was based on the methodology developed by Strelow (2007) entitled "Global Analysis of Journalistic Newspapers" (GAJN). The cyclical nature of this research is shaped by the election of four distinct moments for the study: socio-historical-cultural analysis of the organization, analysis of institutional sites, preparation of strategies for mobilization and reading of signatory companies. In the theoretical basis, we used the authors' notes Ashley (2005), ETHOS Institute (2016), Goldstein (2007), Fisher (2002), Melo Neto and Fróes (1999, 2001) and Tachizawa (2014) for the conceptualization of the third sector and the ETHOS Institute, in addition to the concepts of social responsibility and business ethics. We also explore the concepts of social mobilization, with the authors Henriques (2010, 2013), Mafra (2008) and Toro and Werneck (1997), and of communication strategies, with authors Pérez (2012), Rodrigues (2001) and Tironi e Cavallo (2006). As result of the research, the strategies found on the sites of the ETHOS Institute and the Anti-Corruption Pact were classified as information, security, awareness, convocation and co-responsibility strategies. From the classification, we suggest the relationship with the scale of levels of linkage presented by Henriques (2013). We infer that the mobilization proposed by ETHOS in the Pact against Corruption reaches the fourth level of attachment. Up to this level, the communication strategies are efficient for the mobilization of companies in signing the Pact against Corruption. However, the co-responsibility strategies found in the search for cohesion and continuity of the project seem to be insufficient for a complete mobilization process of the signatories. We then assume that, after becoming a signatory, companies are not engaged in the project, diversifying their performance in the Pact by the already established organizational culture. In addition, this failure in the mobilization process can lead to a distancing of the signatories with the cause proposed by the Pact and the ETHOS Institute's difficulty in monitoring the ethical actions of companies.